Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1175/jcli3601.1
|View full text |Cite
|
Sign up to set email alerts
|

Dipole Structure of Interannual Variations in Summertime Tropical Cyclone Activity over East Asia

Abstract: The present study examines variations in summertime (July–September) tropical cyclone (TC) activity over East Asia during the period 1951–2003. To represent TC activity, a total of 853 TC best tracks for the period were converted to TC passage frequencies (TPFs) within 5° × 5° latitude–longitude grids; TPFs are defined as the percentage values obtained by dividing the number of TC appearances in each grid box by the total number of TCs each year. Empirical orthogonal function analysis of the TPF showed three l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 31 publications
1
34
0
Order By: Relevance
“…In this study, first we identify the years with higher and lower frequency of TC landfall on Japan, and then extract the dominant modes of atmospheric circulation fields over the western North Pacific. To what extent our dominant modes are comparable with the modes identified by Kim et al (2005) will also be examined. Finally, the relationship between the dominant modes is investigated for years with higher and lower frequency of TC landfall.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…In this study, first we identify the years with higher and lower frequency of TC landfall on Japan, and then extract the dominant modes of atmospheric circulation fields over the western North Pacific. To what extent our dominant modes are comparable with the modes identified by Kim et al (2005) will also be examined. Finally, the relationship between the dominant modes is investigated for years with higher and lower frequency of TC landfall.…”
Section: Introductionmentioning
confidence: 91%
“…Similarly, Wang and Chan (2002) showed the relationship between ENSO episodes and TC genesis, but the relationship between ENSO episodes and TC landfall on Japan is to be examined. Recently Kim et al (2005) computed the TC passage frequency at 5 Â 5 grid resolution, and applied the empirical orthogonal function (EOF) analysis to extract the dominant modes of the TC passage. They found that there are three dominant modes; two tropical modes, and a Korea-Japan dipole mode as a third mode, which they referred to as 'East Asian dipole pattern' (EADP).…”
Section: Introductionmentioning
confidence: 99%
“…The La Niñ a phase induces a reversed situation. The difference in the location of genesis in the different phases of ENSO has been explained in terms of large-scale ocean-atmosphere interaction associated with regional changes in sea surface temperature (SST), a vertical wind shear, an extension of the monsoon trough, and relative vorticity anomalies induced by wind anomalies in the lower troposphere (Chen et al 1998;Chan 2000;Chia and Ropelewski 2002;Wang and Chan 2002;Wu et al 2004;Kim et al 2005;Camargo et al 2007b). …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in strong El Niño years, TSs tend to have a higher potential to become generally more intense and long lived because of their formation nearer to the equator than in normal years, allowing a longer period within a warm SST environment (Wang and Chan 2002;Camargo and Sobel 2005;Camargo et al 2007b). These characteristics are induced by large-scale oceanatmosphere interactions associated with regional changes in SST, vertical wind shear, the extension of the monsoon trough, and lower-tropospheric relative vorticity anomalies (Chen et al 1998;Chan 2000;Chia and Ropelewski 2002;Wang and Chan 2002;Wu et al 2004;Kim et al 2005;Camargo et al 2007b;Kim et al 2011). Because of the strong influence of ENSO on TS activity described above, ENSO is generally considered to be the main predictor in seasonal statistical TS prediction models (Chan et al 1998;Chan et al 2001;Wang and Chan 2002;Chan 2003, Lea andSaunders 2006).…”
Section: Introductionmentioning
confidence: 99%